E-Advocacy in the Information Market: How Social Media Platforms Distribute Evidence on Charter Schools. (April 2021) - Castillo, Elise; La Londe, Priya Goel; Owens, Stephen; Scott, Janelle; DeBray, Elizabeth; Lubienski, Christopher
A growing body of research investigates how intermediary organizations (IOs) and their networks navigate, promote, and produce evidence on social media. To date, scholars have underexplored blogs, an important milieu in which IOs produce and disseminate information. In this analysis, we broaden the emerging scholarship on evidence brokering by examining how IOs and individual and independent bloggers broker knowledge via education policy blogs on charter schools and related education policy. Although blogging can potentially enhance knowledge production and dissemination, our findings demonstrate that bloggers often promote research evidence of uneven quality and scientific rigor.